NILAI-NILAI PENDIDIKAN DALAM HUKUM TAKLIF - Kholidah Kholidah (FORUM PAEDAGOGIK, 2015)
Scholl of Islamic law, devide the judical level of accountability (al-ahkam al-Taklim) into five, namely, obligation (wajib), recomended (madub), law/ permissible (mubah), discouraged (makruh) and prohibitted (haram). The oblication and recomendation based on positive order/imperatives (awamori) in the scripts and tended to order the embellished action (hasanah).